Estrategias de Marketing para el Posicionamiento de Marca de una MYPE del Sector Inmobiliario. - Florián Castillo, O.R. (2023)
The objective of the research was to determine different marketing strategies for a SME in the real estate sector, under a mixed approach methodology and a non-experimental design with a cross section. The techniques and instruments used were a survey and an interview. In addition, a questionnaire validated by expert judgment was applied to 55 clients, obtaining a reliability of 0.88 in Cronbach's alpha. From the external diagnosis, a weighting of 2.95 was obtained in the EFE matrix and 2.73 in the EFI matrix; likewise, a score of 2.80 from the MPC matrix. And from the questionnaire it was obtained that more than 60% are female, aged 23 to 40 years; of these, more than 60% use and obtain information from Facebook and Instagram; In addition, 85% consider it essential to maintain traditional advertising. Concluding that strategies such as: Carry out corporate video marketing, automate the level of response of social networks, establish alliances with companies in the same field and implement 360 virtual tours and carry out remarketing; They will help increase the scope of customer acquisition and position the company's brand. Finally, the implementation costs amount to an initial investment of S/ 82057.